Sustainable rainfed crop sequence based on rainfall analysis under semi-arid vertisol - D. R. PADMANI; G. R. MARUTHI SANKAR; K. N. AKBARI; M. S. GAJERA; G. S. SUTARIA; M. K. KHISTARIA (Journal of Agrometeorology, 2009)
Based on field experiments conducted with 12 crop sequences (groundnut-groundnut, groundnut-cotton, groundnut-castor, groundnut-pearl millet, groundnut-sesame, cotton-cotton, cotton-castor, cotton-pearl millet, cottonsesame, castor-castor, pearl millet-pearl millet and sesame-sesame) with 3 fertilizer treatments (control, integrated nutrient management (INM) and recommended dose of fertilizer for different crops) during 1999 to 2005, a statistical selection is made to identify an efficient crop sequence for attaining maximum sustainable yield in a semi-arid Vertisol at Rajkot, Gujarat state. The results revealed that rainfall in individual month, differences of crop sequences, fertilizer treatments and their interaction were significant for groundnut pod equivalent yield. Based on ranking of crop sequences for mean yield and sustainable yield index, groundnut–sesame was found to be highly efficient.